Climate change adaptation strategies among rice farmers in coastal agro-ecological systems - Eka Tuwu; Aminuddin Mane Kandari; La Ode Muhammad Erif; La Gandri; Arfiani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study aims to identify the indicators and impacts of climate change experienced by rice farmers in Lawele Village, a coastal area of Buton Island, and to examine the structural and non-structural adaptation strategies they implement. The research also assesses farmers’ participation in government-led climate adaptation programs. Methods: A descriptive quantitative method was used, involving structured interviews with 30 purposively selected rice farmers. Data were gathered through questionnaires, field observations, and documentation, and analyzed using percentage-based tabulation to describe patterns of climate-related impacts and adaptive responses. Finding: All respondents (100%) reported direct impacts of climate change, including pest outbreaks, declining yields, and crop failure, as well as indirect impacts such as increased production costs and reduced income. Structural adaptation measures primarily involved the construction and maintenance of irrigation channels initiated by the government, with farmers contributing to their upkeep. Non-structural adaptations were practiced universally (100%), including fertilizer application and adjustments to cropping patterns to reduce pest pressure and maintain productivity. However, the adoption of pest-resistant improved varieties remained limited, with only 17 farmers (57%) using them, while 13 farmers (43%) had not, largely due to high seed prices, limited technical assistance, and the absence of continuous support programs. Participation in climate adaptation training was also low, with only 15 farmers (50%) having attended government-led extension activities. Conclusion: Climate change exerts significant direct and indirect pressures on rice farming in Lawele Village. Although farmers have adopted various adaptation strategies, their implementation is hindered by economic constraints, insufficient technical guidance, and limited engagement in training programs. Strengthening institutional support and providing sustained capacity-building initiatives are essential to enhancing the resilience of rice farming systems in this coastal, climate-vulnerable region. Novelty/Originality of this article: This article bridges the experiences of local farmers, adaptation strategies, and institutional participation gaps in the context of coastal rice farming, which has not been widely researched, by providing empirical evidence and insights relevant to policy.